2018
DOI: 10.58327/jstfi.v7i1.71
|View full text |Cite
|
Sign up to set email alerts
|

UJI AKTIVITAS ANTIOBESITAS DARI EKSTRAK ETANOL DAUN MALAKA (Phyllanthus emblica L.) TERHADAP TIKUS PUTIH JANTAN GALUR Wistar

Abstract: Obesitas merupakan penimbunan lemak yang berlebihan di dalam tubuh yang disebabkan oleh asupan jumlah makanan yang lebih besar dari pada yang dapat digunakan untuk energi. Daun Malaka (Phyllanthus emblica L.) merupakan salah satu tanaman berkhasiat obat yang belum banyak diketahui masyarakat digunakan sebagai obat obesitas. Daun malaka mengandung senyawa tanin, flavonoid dan saponin yang mampu menghambat kerja enzim lipase pankreas. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak etanol daun malaka … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…This can occur because of the toxic effects found in mahogany seeds, causing death in one of the five observed rats and several other factors. According to Rasyad et al studies of the acute toxicity test of mahogany seed extract, administration of mahogany seed extract at a dose of 76.44 mg/200 gBB given to mice can be nephrotoxic 32 . Another factor that causes a decrease in the number of macrophages in the presence of essential oils in mahogany seeds is the Tetiana study regarding the decrease of macrophage phagocytosis of mice after stimulated kencur essential oil that the higher concentration of essential oils decreases phagocytic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can occur because of the toxic effects found in mahogany seeds, causing death in one of the five observed rats and several other factors. According to Rasyad et al studies of the acute toxicity test of mahogany seed extract, administration of mahogany seed extract at a dose of 76.44 mg/200 gBB given to mice can be nephrotoxic 32 . Another factor that causes a decrease in the number of macrophages in the presence of essential oils in mahogany seeds is the Tetiana study regarding the decrease of macrophage phagocytosis of mice after stimulated kencur essential oil that the higher concentration of essential oils decreases phagocytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the dosage used, the effectiveness of mahogany seed extract will decrease, such as the optimal way of working alcohol at a concentration of 70% compared to 100%. Pichika in 2015 reported that mahogany seeds were safe for humans at a level of 325 mg/kg body weight in an acute oral toxicity study of Swietenia macrophylla seeds in Sprague Dawley rats in 2015 [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Pakan standar BRAVO 512 sebanyak 20gram dicampur dengan margarin cair yang dipanaskan sebanyak 1,7gram ditempatkan dalam baskom yang diberikan per hari per ekor tikus wistar (Ali et al, 2015). Selain itu, pakan juga ditambah lemak kambing sebanyak 1,5ml yang diblender sampai homogen diberikan melalui sonde oral per hari per ekor tikus wistar (Ardiansyah et al, 2018).…”
Section: Pembuatan Pakan Kaya Lemakunclassified
“…All test materials were diluted in 2 mL of aquadest and then given to the test animals orally using a blunt needle sonde every morning. The dose of OPE given refers to research conducted by Depari et al (2021) with an effective dose of 1000 mg/kgBW in reducing sugar levels in obese rats accompanied by diabetes mellitus, besides that, the dose of orlistat is a standard dose from humans converted to rats (Ardiansyah et al 2018).…”
Section: Ope Interventionmentioning
confidence: 99%